Priming in economics - Alain Cohn; Michel André Maréchal (University of Zurich, Department of Economics, 2016)
Conceptual priming has become an increasingly popular tool in economics. Here, we review the literature that uses priming in incentivized experiments to study economic questions. We mainly focus on the role of social identity, culture, and norms in shaping preferences and behavior. We also discuss recently raised objections to priming research and conclude with promising avenues for future research.
Keywords: C90; D03; 330; Priming; experiment; identity; endogenous preferences